Eksplorasi Teoretis Tentang Motivasi Berprestasi dalam Kewirausahaan: Implikasi untuk Strategi Bisnis - Nailan, Akhmaliah Siti; Sariah, Dedeh; Wahyuni, Femi Sri (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2024)
Achievement motivation is a key factor influencing an individual’s success in entrepreneurship. This article aims to elucidate the definition and foundational theories of achievement motivation within the context of entrepreneurship. Achievement motivation can be defined as an internal drive that propels individuals to reach specific goals and standards deemed important. In entrepreneurship, this motivation serves as a primary driver for individuals to take risks, innovate, and attain business success. The theoretical foundations of achievement motivation include McClelland's need theory, which emphasizes the importance of the need for achievement, affiliation, and power. Additionally, expectancy theory and goal-setting theory contribute to understanding how individuals establish and pursue their objectives in entrepreneurship. This research concludes that a profound understanding of achievement motivation can assist aspiring entrepreneurs in developing effective strategies to achieve business success.